Pengaruh Corporate Social Responsibility, Ukuran Perusahaan, Transfer Pricing dan Sales Growth terhadap Agresivitas Pajak - Ratna Herawati; Agung Prajanto; Dian Indriana Hapsari; Diana Puspitasari (Pusat Riset dan Inovasi Nasional, 2025)
Tax is one of the main sources of revenue in the implementation of the economy in Indonesia. The obligation to pay taxes is following the law but is not in line with the company's main goal of maximizing profits, so companies tend to minimize their tax obligations. The company's action of carrying out tax planning to minimize tax obligations is called tax aggressiveness. This study aims to identify and analyze the factors that influence tax aggressiveness in energy sector companies listed on the Indonesia Stock Exchange for the 2019-2022 period. These factors are corporate social responsibility, company size, transfer pricing, and sales growth. The population in this research is all energy companies listed on the Indonesia Stock Exchange in 2019-2022. The data source used is secondary data in the form of financial reports and sustainability reports. The sampling method used purposive sampling method which resulted in a total sample of 14 companies and a total of 56 data. The analysis technique uses multiple linear regression analysis with classical assumption testing including normality, multicollinearity, heteroscedasticity, and autocorrelation tests. The research results conclude that corporate social responsibility and company size have an effect on tax aggressiveness. Meanwhile, transfer pricing and sales growth have no influence on tax aggressiveness.